Lanskap Linguistik pada Ruang Publik Makam Waliyullah di Madura: Bentuk dan Fungsi Penggunaan Bahasa - Iswah Adriana; Agus Purnomo Ahmad Putikadyanto; Agik Nur Efendi; Nora Erika Aulia (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
Public spaces in the waliyullah gravesites in Madura are deeply embedded with religious and cultural meanings, as reflected in the use of language on signboards, prayers, and other symbolic representations. This study aims to analyze the forms and functions of language use in the public spaces of waliyullah tombs in Madura. The tombs that serve as the focus of this research include the tomb of Syaikhona Cholil in Bangkalan, the tomb of Ratu Ibu in Sampang, the Batu Ampar tomb in Pamekasan, and the Asta Tinggi tomb in Sumenep. This study employs a qualitative approach with data collection techniques including observation, interviews, and documentation. The findings indicate that Indonesian predominantly dominates language use in the public spaces of waliyullah tombs, while Arabic and Madurese are used to represent religious and local cultural identities. The functions of language in these public spaces include an informative function, which provides guidance and regulations, and a symbolic function, which reinforces religious and cultural identities.